TRIANGLE PASE INC. PUBLIC RELATIONS COMMUNICATION STRATEGY. EAST ACEH DISTRICT IN MAINTAINING A CORPORATE IMAGE DURING THE COVID-19 PANDEMIC CRISIS - Ridha Ramadhan, Muhammad; Lubis, Suwardi; Pohan, Syafrudin (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
Sometimes a company is required to deal with certain crisis, and unpredictable incidents which can potentially threaten the company reputation, profits, and/or employee safety and public. Covid-19 which is categorized as non-natural disaster by the Indonesia government can nearly affect the company reputation that has been built as a result of sudden, unpredictable and unsolved crisis. Amid the Covid-19 pandemic, Triangle Pase Inc. has ever received censure from the community for the destruction on roads due to the gas field operation in the residential area. The research problems are the strategy and its application by Tringale Pase Inc. during the crisis in order to maintain the company image as well as the obstacles encountered. The research uses the Coombs' crisis communication theory and descriptive qualitative method. The research informants consist of one main informant from Internal employee of Tringale Pase Inc. in East Aceh and four supporting informants who lives around the company area. Data are collected through interviews, observation, and documentation. The result indicates that communication strategy used by Tringale Pase Inc. consist of three stages namely pre-crisis, crisis, and post-crisis. The obstacles encountered by Triangle Pase Inc. come from the internal factors namely the obstacles of human resources, facilities and infrastructures, and finance. Meanwhile, the external factor namely communication to community obstacle due to low educational level and community adherence. Data are collected through interviews, observation, and documentation. The result indicates that communication strategy used by Tringale Pase Inc. consist of three stages namely pre-crisis, crisis, and post-crisis. The obstacles encountered by Triangle Pase Inc. come from the internal factors namely the obstacles of human resources, facilities and infrastructures, and finance. Meanwhile, the external factor namely communication to community obstacle due to low educational level and community adherence. Data are collected through interviews, observation, and documentation. The result indicates that communication strategy used by Tringale Pase Inc. consist of three stages namely pre-crisis, crisis, and post-crisis. The obstacles encountered by Triangle Pase Inc. come from the internal factors namely the obstacles of human resources, facilities and infrastructures, and finance. Meanwhile, the external factor namely communication to community obstacle due to low educational level and community adherence. and finance. Meanwhile, the external factor namely communication to community obstacle due to low educational level and community adherence. and finance. Meanwhile, the external factor namely communication to community obstacle due to low educational level and community adherence.